Genetic and phenotypic spectrum of Chinese patients with epilepsy and photosensitivity - Niu, Yue; Gong, Pan; Jiao, Xianru; Xu, Zhao; Zhang, Yuehua; Yang, Zhixian (Frontiers in Neurology, 2022)
Objective: To determine the contribution of genetic etiologies in epilepsy with photosensitivity. Methods: A total of 35 epileptic patients with genetic photosensitivity from January 2019 to May 2021 were analyzed. Results: Pathogenic variants were identified in 35 patients, including SCN1A(7) CHD2(6), TPP1(3), SYNGAP1(3), GABRA1(2), GABRG2(1), KCTD7(1), MFSD8(1), KCNC1(1) GBA(1), CACNA1A(1), KCNMA1(1), FLNA(1), SZT2(1), SLC2A1(1), 5q33.2-34del(1), and mitochondrial variants(3). The predominant epileptic syndrome was progressive myoclonus epilepsy (PME) and Dravet syndrome, while the most common seizure type in both spontaneous seizures and photoconvulsive response (PCR) was myoclonic seizures. The abnormal EEG background and brain MRI were mainly seen in the PME patients. In PME, initial low-frequencies (1-6 Hz) photosensitivity was observed in 70% (7/10) of patients. Among the other patients, 12 patients (48.0%, 12/25) had photosensitivity at initial low -frequencies and 12 patients (48.0%, 12/25) had photosensitivity at initial middle frequencies (6-20 Hz). At the one-year follow-up, 77.7% (21/27) still remained photosensitive. Conclusion: The most common genes for epilepsy with genetic photosensitivity are SCN1A and CHD2, and the most common syndromes are PME and Dravet syndrome. MFSD8, KCNMA1, SZT2, FLNA, and SLC2A1 variants might be candidate genes for photosensitivity. PPRs at initial low-frequencies may be a marker of PME, and the most typical feature of genetic photosensitivity may be low- or middle- frequencies induced PPRs. Photosensitivity in epilepsy with genetic photosensitivity may be difficult to disappear in a short period of time.